A Composite Score Summarizing Use and Dosing of Evidence-Based Medical Therapies in Heart Failure: A Nationwide Cohort Study. (25th January 2023) - Johansen, Niklas Dyrby; Vaduganathan, Muthiah; Zahir, Deewa; Fiuzat, Mona; DeFilippis, Ersilia M.; Januzzi, James L.; Butler, Javed; O'Connor, Christopher M.; Abraham, William T.; Psotka, Mitchell A.; McMurray, John J.V.; Dewan, Pooja; et al.
Abstract : Background: As heart failure therapeutic care becomes increasingly complex, a composite medical therapy score could be useful to conveniently summarize background medical therapy. We applied the composite medical therapy score developed by the Heart Failure Collaboratory (HFC) to the Danish heart failure with reduced ejection fraction population to evaluate its external validation including assessing the distribution of the score and its association with survival. Methods: In a retrospective nationwide cohort study, we identified all Danish heart failure with reduced ejection fraction patients alive on July 1, 2018, and assessed their treatment doses. Patients were excluded if they did not have at least 365 days for up-titration of medical therapy prior to identification. The HFC score (range 0–8) accounts for use and dosing of multiple therapies prescribed to each patient. Risk-adjusted association between the composite score and all-cause mortality was examined. Results: In total, 26 779 patients (mean age 71.9 years; 32% women) were identified. At baseline, angiotensin-converting enzyme inhibitor/angiotensin receptor blocker was used in 77%, β-blocker in 81%, mineralocorticoid receptor antagonist in 30%, angiotensin receptor-neprilysin inhibitor in 2%, and ivabradine in 2%. The median HFC score was 4. After multivariable adjustment, higher HFC scores were independently associated with lower mortality (≥median versus <median: hazard ratio, 0.72 [0.67–0.78]; P <0.001). In restricted cubic spline analysis based on a fully adjusted Poisson regression model, a graded inverse association between the HFC score and death was observed, P <0.001. Conclusions: Nationwide assessment of therapeutic optimization in heart failure with reduced ejection fraction using the HFC score was feasible and the score was strongly and independently associated with survival.